Electronic books versus paper books: Pre-service teacher preference for University study and recreational reading - Johnson, Genevieve; Buck, G. (ARC (Academics Research Centre), 2014)
Publishing trends suggest that electronic books or e-books are the future of reading. Since teacher reading attitudes influence student reading attitudes, it is important to understand patterns of e-book use among pre-service teachers. One hundred ninety-nine pre-service teachers complete an online questionnaire that queried use of e-books and paper books or p-books. While the majority of pre-service teachers expressed preference for b-books both for university study and for recreational reading, a shift in relative proportion was apparent. That is, 27% of pre-service teachers did not report a preference for p-books over e-books for recreational reading; 14% did not report a preference for p-books over e-books for university study. Teacher educators might present their students with improved e-book learning strategies, not only because digital technologies facilitate literacy but also because teachers should promote forms of literacy consistent with life after the digital revolution.